From Bench to Bedside and Back – Report on the European Helicobacter pylori Study Group Xth International Workshop on Gastroduodenal Pathology and Helicobacter pylori - ABR Thomson; N Chiba; P Sinclair (Canadian Journal of Gastroenterology)
The Xth International Workshop on Gastroduodenal Pathology and Helicobacter pylori was held in Lisbon, Portugal, from September 12 to 14, 1997. State-of-the-art reviews and research findings were presented to over 2000 participants. This review focuses on important new developments and serves as a rapid communication of clinically relevant material.